Analisis Penilaian Kinerja Organisasi Perangkat Daerah Di Kota Bandung (Studi Kasus Pada Dinas Pemakaman & Pertamanan; Dinas Kependudukan & Pencatatan Sipil dan Dinas Pemuda dan Olahraga) - Endah Purnama Sari; Santy Setiawan; Alif Rifky Adilah (Universitas Kristen Maranatha, 2017)
AbstractÂ The realization of a good and accountable governance is the hope of all parties. It is expected that the development and implementation of an accountability system that is accurate, clear, legitimate so that the government and development can be carried out efficiently, effectively, cleanly and responsibly and free from corruption, collusion and nepotism (KKN). Based on SpeklÃ© and Verbeeten (2013) studies indicating that contractibility moderates the relationship between the use of performance-oriented system performance incentives. The use of performance measurement systems for the purpose of negative incentives affects organizational performance, but this effect is too heavy when Contractibility is high. The type of this research is causal explanatory, and the research sample is population 3 SKPD (Work Unit of Local Area) located in Bandung with data analysis technique using Moderated Regression Analysis (MRA) or interaction test is a special application of linear regression where in regression equation contain Elements of interaction (multiplication of two or more independent variables).Â Keywords: Performance Appraisal System, Performance, Contractibility, SKPD Bandung, Public Sector